2022
DOI: 10.3390/ijerph19031694
|View full text |Cite
|
Sign up to set email alerts
|

Factors Worsening and Mitigating the Consequences of the COVID-19 Outbreak on the Overall Health of Informal Caregivers of Older People with Long-Term Care Needs Living in Germany and in Italy

Abstract: Population ageing and the higher prevalence of multimorbidity in later life are increasing the demand for Long-Term Care (LTC) worldwide; this has been exacerbated by the COVID-19 pandemic. As in Europe and beyond, the bulk of care for frail older people is carried out by informal caregivers. This study aimed at understanding the factors affecting the overall worsening health of informal caregivers of older people with LTC needs living in Germany and Italy during the outbreak. To this purpose, 319 informal car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…Studies from various countries show that gender (Lorenz‐Dant & Comas‐Herrera, 2021 ; Raiber & Verbakel, 2021 ; Zwar et al, 2022 ), age (Budnick et al, 2021 ; Hofstaetter et al, 2022 ), employment (Truskinovsky et al, 2022 ), living situation of the care recipient (Prins et al, 2021 ; Smaling et al, 2022 ), relationship to the care recipient (Tur‐sinai et al, 2021 ) and network (Allen et al, 2022 ) were important characteristics that distinguish how caregivers were affected. Studies in the Netherlands found that there were differences between men and women, and between those in different relationships to the care recipient (Prins et al, 2021 ; Raiber & Verbakel, 2021 ; Smaling et al, 2022 ; Tur‐sinai et al, 2021 ) Previous literature thus shows that consequences differed across countries, which may be due to differences in measures, COVID impact and healthcare system (Lorenz‐Dant & Comas‐Herrera, 2021 ; Santini et al, 2022 ; Tur‐sinai et al, 2021 ). In the Netherlands, there were relative large increases in informal care and decreases in formal care compared to other countries (Tur‐sinai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies from various countries show that gender (Lorenz‐Dant & Comas‐Herrera, 2021 ; Raiber & Verbakel, 2021 ; Zwar et al, 2022 ), age (Budnick et al, 2021 ; Hofstaetter et al, 2022 ), employment (Truskinovsky et al, 2022 ), living situation of the care recipient (Prins et al, 2021 ; Smaling et al, 2022 ), relationship to the care recipient (Tur‐sinai et al, 2021 ) and network (Allen et al, 2022 ) were important characteristics that distinguish how caregivers were affected. Studies in the Netherlands found that there were differences between men and women, and between those in different relationships to the care recipient (Prins et al, 2021 ; Raiber & Verbakel, 2021 ; Smaling et al, 2022 ; Tur‐sinai et al, 2021 ) Previous literature thus shows that consequences differed across countries, which may be due to differences in measures, COVID impact and healthcare system (Lorenz‐Dant & Comas‐Herrera, 2021 ; Santini et al, 2022 ; Tur‐sinai et al, 2021 ). In the Netherlands, there were relative large increases in informal care and decreases in formal care compared to other countries (Tur‐sinai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, until the present study, no comprehensive representative study of the ICs of older adults had been conducted in Slovenia to investigate the caregiving situation and burden of older people’s ICs. While many studies conducted during the pandemic were based on selective and convenience samples (e.g., [ 43 , 44 ]), we conducted a study with a sample from the general population to enable generalization of the results. Therefore, the first aim of the present study, conducted after the first year of COVID-19 in Slovenia, was to determine the caregiving situation and burden during the outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…However, the understanding of caregiving situations varies widely among the studies [ 57 , 58 , 59 , 60 ], and they are often vaguely defined [ 61 , 62 , 63 , 64 , 65 ]. Second, the impact of the pandemic on the ICs of older people has been investigated in several studies [ 43 , 44 , 47 , 66 , 67 , 68 , 69 , 70 ], but not the caregiving situation characteristics and subjective burden during the pandemic phase in 2021. Therefore, the second aim of our study was to clearly and holistically define the caregiving situation based on the conservation of resources theory [ 71 ], understanding the objective burden [ 72 , 73 ], and the overview presented in Section 1.2 , and to investigate how the caregiving situation’s characteristics predict the subjective burden.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations